2017
DOI: 10.7717/peerj.3199
|View full text |Cite
|
Sign up to set email alerts
|

A link between central kynurenine metabolism and bone strength in rats with chronic kidney disease

Abstract: BackgroundDisturbances in mineral and bone metabolism represent one of the most complex complications of chronic kidney disease (CKD). Serotonin, a monoamine synthesized from tryptophan, may play a potential role in bone metabolism. Brain-derived serotonin exerts a positive effect on the bone structure by limiting bone resorption and enhancing bone formation. Tryptophan is the precursor not only to the serotonin but also and primarily to kynurenine metabolites. The ultimate aim of the present study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…These alterations may be associated with the pathological changes in bone structure. In contrast to the central kynurenines (Kalaska et al, 2017 ), we observed the negative relationships between serum level of kynurenine and bone biomechanical as well as geometrical parameters. These associations may suggest unfavorable effects of peripheral kynurenine pathway metabolites on bone structure and may develop new strategies for the treatment, prevention, and diagnosis of osteoporosis in CKD patients.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…These alterations may be associated with the pathological changes in bone structure. In contrast to the central kynurenines (Kalaska et al, 2017 ), we observed the negative relationships between serum level of kynurenine and bone biomechanical as well as geometrical parameters. These associations may suggest unfavorable effects of peripheral kynurenine pathway metabolites on bone structure and may develop new strategies for the treatment, prevention, and diagnosis of osteoporosis in CKD patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Before biomechanical testing, left tibias were thoroughly thawed to room temperature. The biomechanical properties of left tibias were determined using the three-point-bending test as described previously (Brzoska et al, 2005 ; Kalaska et al, 2017 ). The testing was performed with a testing machine Zwick Roell Z.2.5 (Germany) using testXpert II software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also significant upregulation of expression of the AhR gene, presumably the mediator of KYN effects. In contrast to peripheral effects, central kynurenine metabolism (similarly to serotonin) may have a beneficial impact on bone parameters in the setting of renal insufficiency [73]. Rats undergoing partial nephrectomy were found to have a significant elevation in KYN with a decrease in tryptophan levels in brain areas examined (cerebellum, brainstem, frontal cortex, hypothalamus and striatum) and an increase in tibial cross-sectional area and wall thickness.…”
Section: The Dual Role Of Serotonin In Bone Homeostasismentioning
confidence: 99%
“…42,191,192 Evidence for the accumulation of the metabolites of the kynurenine pathway in the course of chronic renal insufficiency and their impact on bone tissue, prompted some researchers, including our team, to deal with the topic of connections between the CKD, changes in kynurenine system activation and bone metabolism. 31,35,98,187,[192][193][194] In vitro studies have proven, that the accumulation of KYN and 3-HKYN in bone marrow stromal cells (BMSCs) have been associated with a decrease in cell proliferation and differentiation, though the mechanism which is directly mediated by their pro-oxidative properties. Microarray analysis identified 50 upregulated, and 36 downregulated micro RNAs (miRNAs) in KYN-treated BMSCs.…”
Section: Associations Between the Increased Activity Of The Kynureninmentioning
confidence: 99%